Characterization of immune cell populations in the male reproductive tract of the mouse - Kumar, Vishnu; Justus Liebig University Giessen (My University, 2024)
Infertility affects about 15% of couples globally, with male factors accounting for half of all instances. Infection and inflammation of the male reproductive tract contribute to about 15% of male infertility. Various pathogens, including bacteria, viruses, and parasites, infect the male reproductive organs and induce inflammation. Especially, bacteria can infect the male reproductive organs, causing testicular damage, epididymitis, prostatitis, and urethritis. Various bacteria and viruses such as Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma spp., HIV, and HPV are found in semen and can also infect females through sexual transmission. Sterile inflammation, possibly of auto-immne origin, is another etiology of the infertility, with approximately 25% of testicular biopsies from infertile men showing focal inflammatiory lessions. The immune system plays an important role in the survival of organisms by protecting against pathogens and maintaining tissue homeostasis. The immune system and the composition of immune cells in the male reproductive organs are not well-explored. Male infertility is increasingly being recognized as a predictor for overall male health, due to higher predisposition for comorbidities. This highlights the importance of investigating the immune cell landscape in male reproductive organs. Therefore, this study characterized the immune cell composition within the male reproductive organs of C57BL/6J mice using flow cytometry and immunofluorescence analyses. In all male reproductive organs, except the penis, macrophages are the predominant immune cells. In the penis, B cells and neutrophils are more prominent, indicating exposure to environmental immune stimuli. Moreover, our findings suggest that the main source of B cells in the penis is mostly concentrated in its bone region. Dendritic cells are present in lower frequencies in all male reproductive organs. However, seminal vesicles harbour more T, NK, and NKT cells than other male reproductive organs. Next, the contribution of blood monocytes to the resident macrophage population in MROs was identified. Our analysis using the Ccr2gfp/gfp KI/KO mouse model revealed that in seminal vesicles, urethra, and penis, a subset of the macrophage population is derived from bone marrow-derived monocytes. Furthermore, macrophages in the male reproductive organs of C57BL/6J mice were depleted using the PLX5622 CSF1R inhibitor to determine their function in normal homeostasis. Over 90% of macrophages were depleted in the testis, epididymis, vas deferens, and seminal vesicle, while in the prostate, urethra, and penis, effectiveness was less than 70%. After ten days of macrophage depletion, no gross histological changes were observed. However, Azan staining showed the appearance of collagen deposition in the testis and epididymis, and a reduction in the urethra. Moreover, this study identified a novel macrophage population (F4/80hiCD11b-) in the seminal vesicles and prostate, emerging in 6 week old mice (puberty period). This is the first study to characterize the complexity of the immune cell population in the entire male reproductive organs. Altogether, this indicates that immune cell diversity, macrophage heterogeneity, and their functions are tissue-specific and may be influenced by tissue microenvironments.